2014 10th France-Japan/ 8th Europe-Asia Congress on Mecatronics (MECATRONICS2014- Tokyo) 2014
DOI: 10.1109/mecatronics.2014.7018555
|View full text |Cite
|
Sign up to set email alerts
|

Finding energy-efficient paths on uneven terrains

Abstract: Abstract-Mobile robots are increasingly getting popular in outdoor applications. Long period of continuous operations are common in such applications. Therefore, robot motions need to be optimized to minimize their energy consumption. Shortest paths do not always guarantee minimum energy consumptions of mobile robots. This paper proposes a novel algorithm to generate energyefficient paths on uneven terrains using an established energycost model for mobile robots. Terrains are represented using grid based eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…In [31], the authors showed that A* with such a heuristic function is unable to find physically feasible paths on steep terrains because heuristics can sometime be infinitely large depending on the gradient of the straight line connecting current location and goal location. Recently, we proposed a heuristic search algorithm (basic Z*) for energy-efficient path planning on simulated grid-based elevation maps [33]. Its heuristics can overcome the impermissible traversal headings due to power limitations of a mobile robot.…”
Section: A Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In [31], the authors showed that A* with such a heuristic function is unable to find physically feasible paths on steep terrains because heuristics can sometime be infinitely large depending on the gradient of the straight line connecting current location and goal location. Recently, we proposed a heuristic search algorithm (basic Z*) for energy-efficient path planning on simulated grid-based elevation maps [33]. Its heuristics can overcome the impermissible traversal headings due to power limitations of a mobile robot.…”
Section: A Related Workmentioning
confidence: 99%
“…Its heuristics can overcome the impermissible traversal headings due to power limitations of a mobile robot. Results given in [33] show that the basic Z* can find energy-efficient paths on uneven terrains where A*-E opt may fail due to infinitely large heuristic energycost. However, the computational efficiency of the basic Z* algorithm may vary due to regular node revisits while searching for an optimal solution.…”
Section: A Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Current research focuses on the autonomous movement of vehicles in a dynamic environment, full of terrain obstacles [ 44 , 45 , 46 ]. Understandably, scientists pay special attention to considering obstacles caused by terrain formation, hence a large number of publications include Digital Terrain Models in the presented methodologies [ 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%